Legal Protection for Victims of Corporate Crimes In The Employment Field at Palembang City - Burhanuddin Burhanuddin (Fakultas Syariah dan Hukum, UIN Syarif Hidayatullah Jakarta, 2017)
Criminal sanctions which are imposed on corporations committing employment crimes as provided inArticle 185 paragraph (1) of the Manpower Act are sufficiently burdensome, both for corporations andcorporate administrators, as the cumulative and alternative system of criminal imposition of criminalpenalties. It means that the corporate executives who commit crimes may be subject to imprisonmentor criminal penalties and both imprisonment and fine. But in practice law enforcement officers do notdirectly impose criminal sanctions in the form of imprisonment to corporate executives who commitcrimes in the field of employment in the city of Palembang. This is due to the tendency of lawenforcement officers to use the principle of subsidiarity, namely the criminal law placed in the ultimumremendium position, on the grounds of economic considerations, so that sanctions are imposed onlyadministrative sanctions and criminal penalties and close the normative rights of labor only. DOI: 10.15408/jch.v5i2.7087